2005
DOI: 10.1016/j.quaint.2005.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Fluvial stratigraphy and palaeoenvironments in the Pasinler Basin, eastern Turkey

Abstract: Valley floor sediments from the Pasinler Basin, eastern Turkey, provide evidence for Pleistocene and Holocene floodplain conditions. Three terrace surfaces are present.Evidence for tectonic processes active during the Late Neogene are widespread within the basin but do not appear to have substantially influenced the detail of the Holocene palaeoenvironmental record. Significant changes in hydrology are recorded, with more stable floodplain conditions occurring at around 9,000, 5,500 and 4,000 cal. yr. BP. Inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Such clay can be deposited under high-energy conditions and therefore contains grains of different size. Collins et al (2005Collins et al ( , 2008 have reported such high-energy sedimentation conditions for Pasinler basin. Thus, a significant proportion of the coarse inclusions contained in the Kura-Araxes Ware from Sos Höyük may be of natural origin, embedded within clay bodies as residue from rock weathering.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Such clay can be deposited under high-energy conditions and therefore contains grains of different size. Collins et al (2005Collins et al ( , 2008 have reported such high-energy sedimentation conditions for Pasinler basin. Thus, a significant proportion of the coarse inclusions contained in the Kura-Araxes Ware from Sos Höyük may be of natural origin, embedded within clay bodies as residue from rock weathering.…”
Section: Discussionmentioning
confidence: 90%
“…During the PlioePleistocene, the basin was subject to a compressive tectonic regime and this continues to the present (Ş engör and Kidd, 1979;Ş engör and Yılmaz, 1981;Dewey et al, 1986). Consequently, tilting and subsidence have permitted accumulation of the thick, lacustrine deposits and extensive Pleistocene and Holocene clastic sediments that underlie much of the present basin floor (Collins et al, 2005(Collins et al, , 2008. The main drainage network and various tributaries send terrigenous materials into the Pasinler basin.…”
Section: Geological Settingmentioning
confidence: 99%
“…The final sedimentary infill comprises Pliocene to Pleistocene lacustrine deposits and extensive Pleistocene to Holocene fluvioterrestrial siliciclastics that directly underlie much of the present-day valley floor (Collins et al, 2005(Collins et al, , 2008 (Figure 1b). These 2 lithological units correspond to the Horasan Beds and Pasinler Beds of Irrlitz (1972), respectively.…”
mentioning
confidence: 99%
“…Research on fluvial systems from the eastern Mediterranean area suggests that wetter periods frequently produce continuous sedimentation, while incision and flooding seem to occur during drier periods and/or climate transitions. For example in southern Anatolia (which is the most well-documented and the closest area to Cyprus), three periods of floodplain sedimentation, related to humid conditions which have been recorded (at cal 7000, 3500 and 2000 BC), were followed by phases of vertical incision (Collins et al 2005). In the Lake Tuz area (central Turkey), two major periods of alluvial fan formation associated with a relatively wet climate have been recognised, a major one between cal 5000 and 3500 BC and a minor one around cal 2300 BC (Kashima 2002).…”
Section: Regional and Local Holocene Environmental Changementioning
confidence: 99%